(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
This article describes the problem of finding new techniques and ways to increase motivation for learning foreign languages. One of these forms is new pedagogical technologies, the implementation of which contributes to effective language learning. The article defines the concepts of "Pedagogical Technology" and "Smart Education", which are capable of providing a high level of education corresponding to the tasks and opportunities of today’s world, will allow young people to adapt to a rapidly changing, unstable environment, will ensure the transition from book content to active content using a single common repository of educational materials with an analytical search system; an example of working with the site "die deutsche Welle" is given